MENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA PEMBELAJARAN MATEMATIKA MATERI BANGUN DATAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN NUMBER HEAD TOGETHER - Putri, Vani Angraini; Otaya, Lian G.; Nadjamuddin, Asriyati (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2025)
AbstractThe purpose of this study is to improve the learning outcomes of fifth grade students in learning mathematics on flat shapes using the Number Head Together (NHT) learning model. This type of research is Classroom Action Research (CAR). CAR is a research conducted by teachers in the classroom (school) where they teach with an emphasis on improving or enhancing the learning process and practice. The Number Head Together (NHT) learning model can improve student learning outcomes in learning mathematics on flat shapes. This can be seen from the results of the pre-cycle test with a classical percentage of 20%, then the action was carried out in cycle 1 using the model which increased to 33%, then to get the percentage of completeness, the action was continued in cycle II and the results were 80%, meaning that it had increased and achieved the expected results. Learning models that aim to involve students in the world of education are very numerous and varied, one of which is the Number Head Together (NHT) learning model, where this learning involves many students, both individual and group work, in addition by working and thinking together students know more about the learning material, students are also more active and enthusiastic in following the learning. Keywords: Number Head Together (NHT) Model, Plane Building, Mathematics